Implementation of 20 nm Graphene Channel Field Effect Transistors Using Silvaco TCAD Tool to Improve Short Channel Effects over Conventional MOSFETs - Tayade, Vinod Pralhad; Lahudkar, Swapnil Laxman (Advances in Technology Innovation, 2021)
In recent years, demands for high speed and low power circuits have been raised. As conventional metal oxide semiconductor field effect transistors (MOSFETs) are unable to satisfy the demands due to short channel effects, the purpose of the study is to design an alternative of MOSFETs. Graphene FETs are one of the alternatives of MOSFETs due to the excellent properties of graphene material. In this work, a user-defined graphene material is defined, and a graphene channel FET is implemented using the Silvaco technology computer-aided design (TCAD) tool at 100 nm and scaled to 20 nm channel length. A silicon channel MOSFET is also implemented to compare the performance. The results show the improvement in subthreshold slope (SS) = 114 mV/dec, ION/IOFF ratio = 14379, and drain induced barrier lowering (DIBL) = 123 mV/V. It is concluded that graphene FETs are suitable candidates for low power applications.